Use of identification wristbands among patients receiving inpatient treatment in a teaching hospital - Louíse Viecili Hoffmeister; Gisela Maria Schebella Souto de Moura (Universidade de São Paulo, 2015)
OBJECTIVE: to evaluate the use of identification wristbands among patients hospitalized in inpatient units.METHOD: quantitative, descriptive and transversal research, with a sample of 385 patients. Data collection occurred through the observational method through the filling out of a structured questionnaire which aimed to check the presence of the identification wristband and the identifiers used. Descriptive statistics with absolute and relative frequencies was used for analysis.RESULTS: it was obtained that 83.9% of the patients were found to have the correctly identified wristband, 11.9% had a wristband with errors, and 4.2% of the patients were without a wristband. The main nonconformities found on the identification wristbands were incomplete name, different registration numbers, illegibility of the data and problems with the physical integrity of the wristbands.CONCLUSION: the study demonstrated the professionals' engagement in the process of patient identification, evidencing a high rate of conformity of the wristbands. Furthermore, it contributed to identify elements in the use of wristbands which may be improved for a safe identification process.